2014
DOI: 10.1007/s10067-014-2502-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography is useful to detect subclinical synovitis in SLE patients without musculoskeletal involvement before symptoms appear

Abstract: The purpose of this study is to investigate the frequency of the subclinical synovitis in hand or wrist joints of the SLE patients using ultrasonography (US) and to correlate them with clinical parameters. Forty-eight systemic lupus erythematosus (SLE) patients without musculoskeletal (MS) involvement were enrolled and underwent clinical and laboratory examinations. Gray-scale and power Doppler (PD) US was performed for imaging the wrist, second and third metacarpophalangeal (MCP) joints, and flexor tendons on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 27 publications
1
48
1
Order By: Relevance
“…Compared with the study of Yoon et al,14 our study detected a higher prevalence of SH (grade≥1) in asymptomatic patients with SLE. While the previous study identified joint effusion and/or SH in 58% of asymptomatic patients with SLE, we detected SH (grade ≥1) in 77% asymptomatic patients with SLE.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Compared with the study of Yoon et al,14 our study detected a higher prevalence of SH (grade≥1) in asymptomatic patients with SLE. While the previous study identified joint effusion and/or SH in 58% of asymptomatic patients with SLE, we detected SH (grade ≥1) in 77% asymptomatic patients with SLE.…”
Section: Discussioncontrasting
confidence: 91%
“…While a number of studies have recently described US findings in the SLE population, only some of these included patients who did not complain of musculoskeletal symptoms at the time of the US evaluation,5 35–39 and, to our knowledge, only one focused on asymptomatic patients 14. In these studies, the prevalence of US abnormalities in asymptomatic patients with SLE varied from 3% to 58% 5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations